Review on Iranian Medicinal Plants with Antioxidant Properties - M Khanahmadi; Sh Rezazadeh (Institue of Medicinal Plants, ACECR, 2010)
Antioxidants have important preventive roles, not only on undesirable changes in the flavor and nutritional quality of food, but also on tissue damage in various human diseases. Some of Iranian plants, despite wide spread use of them as medicines in Iran have been investigated for their beneficial use as an antioxidants or source of antioxidants. The present review deals with a list of such plants based on information collected from various literatures dealing with herbs found in Iran having antioxidant properties. Also a brief review on common methods for evaluating anti-oxidant capacity is presented.